Reduction of natural killer but not effector CD8 T lymphocytes in three consecutive cases of severe/lethal H1N1/09 influenza A virus infection. - Denney, L; Aitken, C; Li, C; Wilson-Davies, E; Kok, W; Clelland, C; Rooney, K; Young, D; Dong, T; McMichael, A; Carman, W; Ho, L (Public Library of Science, 2010)
BACKGROUND: The cause of severe disease in some patients infected with pandemic influenza A virus is unclear. METHODOLOGY/PRINCIPAL FINDINGS: We present the cellular immunology profile in the blood, and detailed clinical (and post-mortem) findings of three patients with rapidly progressive infection, including a pregnant patient who died. The striking finding is of reduction in natural killer (NK) cells but preservation of activated effector CD8 T lymphocytes; with viraemia in the patient who had no NK cells. Comparison with control groups suggests that the reduction of NK cells is unique to these severely ill patients. CONCLUSION/SIGNIFICANCE: Our report shows markedly reduced NK cells in the three patients that we sampled and raises the hypothesis that NK may have a more significant role than T lymphocytes in controlling viral burden when the host is confronted with a new influenza A virus subtype.